2016
DOI: 10.1145/2871196
|View full text |Cite
|
Sign up to set email alerts
|

The Ethics of Computing

Abstract: Computing technologies and artifacts are increasingly integrated into most aspects of our professional, social, and private lives. One consequence of this growing ubiquity of computing is that it can have significant ethical implications that computing professionals need to be aware of. The relationship between ethics and computing has long been discussed. However, this is the first comprehensive survey of the mainstream academic literature of the topic. Based on a detailed qualitative analysis of the literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(41 citation statements)
references
References 107 publications
0
40
0
1
Order By: Relevance
“…In 2016, Stahl and colleagues published a paper which provided the first comprehensive systematic review of the academic literature on the ethics of computing (Stahl et al 2016). This paper examined academic publications published between 2002 and 2012 having to do with the ethics of computing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, Stahl and colleagues published a paper which provided the first comprehensive systematic review of the academic literature on the ethics of computing (Stahl et al 2016). This paper examined academic publications published between 2002 and 2012 having to do with the ethics of computing.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of this paper found that a wide range of topics related to ethics of computing were covered, and that there was focused coverage of many different technologies. However, they also concluded that discussion of the methodologies, recommendations, and contributions of papers was lacking (Stahl et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…(106) on AI in healthcare, for instance, concerns of trust, 'traceability' (aligning with what we have labelled 'accountability'), and bias emerged. While privacy and security were explicitly excluded from their review (106), these very issues were a signi cant nding in a systematic review by Stahl et al (107), both with regard to data privacy and personal (or physical) privacy. Issues of the autonomy and agency of AI machines, the challenge of trusting algorithms (linked with their lack of transparency), as well as others that were more closely associated with non-AI computing technologies were also discussed (107).…”
Section: Cross-cutting Themes and Asymmetriesmentioning
confidence: 99%
“…These papers continue to reflect the breadth of issues that constitute the body of work in the field. As our recent review of the computing-oriented literature has shown (Stahl, Timmermans, & Mittelstadt, 2016), privacy and data protection remain the biggest topic in the area. This is reflected in the second issue of the ORBIT journal which carries several papers that look at privacy in social networks (Chutikulrungsee & Burmeister, 2017), brain-computer interfaces (Wahlstrom, Fairweather, & Ashman, 2017), cultural differences in data sensitivity (Fukuta, Murata, Adams, Orito, & Palma, 2017) and legal aspects of privacy in US law (Robison, 2017).…”
Section: Orbit Journal Issue 1:2mentioning
confidence: 99%